Chemical Analysis and Bioactivities of Gaultheria procumbens L. Essential Oil: Herbicidal, Antioxidant and Antibacterial Activities - Sumonrat Jintanasirinurak; Nutcha Manichart; Naphat Somala; Chamroon Laosinwattana; Montinee Teerarak (Current Applied Science and Technology, 2023)
The chemical composition of wintergreen (Gaultheria procumbens L.) essential oil (WEO) was identified by gas chromatography-mass spectrometry (GC-MS) and evaluated for its biological activities. Methyl salicylate (100%) was the main compound in the wintergreen essential oil. The herbicidal efficacy of the WEO was confirmed by germination inhibition, radical and shoot length reduction, and phytotoxicity assessment with Echinochloa crus–galli and Amaranthus tricolor seedlings. The WEO significantly reduced the germination and seedling growth of both weeds. It showed highly significant inhibition of seed germination (93.37%) and seedling growth of A. tricolor at the highest dose (6 µL/petri dish) assayed. The WEO was formulated as an emulsifiable concentrate (EC-EO) for post-emergence application, and was applied at a range of concentrations from 10 to 80 mL/L. Both treated plant leaves appeared wilted and slightly discolored within 1 day of application (DAA). The visible weed control efficacy was most remarkable at 80 mL/L treatment, which was a level that ultimately killed the seedlings of both species at 3 DAA, suggesting promising herbicidal potential for the WEO. The WEO showed weak scavenging activity with a high IC50 value (IC50 >2"×" 104 and >5"×" 104 ppm) for DPPH scavenging and metal chelating assays, respectively. The WEO showed moderate antibacterial activity, and its zones of inhibition against bacterial test strains were 7.90±0.8 mm and 23.9±0.9 mm for Escherichia coli TISTR 780 and Staphylococcus aureus TISTR 1466, respectively. Therefore, the results suggest the possibility of using WEO as an active ingredient to produce natural herbicides.
Keywords: Allelopathy and phytotoxic interactions; Plant Parasitism and Resistance; Plant and animal studies